Prediction of Mechanical Properties of 6061 aluminum Alloy After Heat Treatment Based on GA-BP Neural Network - Long, Zhenyu; Xiao, Feng; Xu, Wangli (International Journal of Computer Science and Information Technology, 2024)
To study the influence of the heat treatment process on the mechanical properties of 6061 aluminum alloy, a prediction model of the mechanical properties of 6061 aluminum alloy after heat treatment based on the GA-BP neural network was established. Based on this model, a set of simple and easy-to-operate built-in data prediction systems was designed. The correlation coefficient R of the GA-BP model was 0.98869, 0.98282, 0.93975, and 0.95657, respectively, and the prediction effect was good. Comparing the predicted value with the experimental value in the prediction system, it is concluded that the prediction accuracy reaches 95.6%, which proves that the model and system have certain stability and feasibility. In addition, this study provides an empirical reference for exploring the effects of solution temperature, cooling rate, aging temperature, and aging duration on the properties of aluminum alloys.